Influence of hydrothermal factors on a coniferous forest canopy in the semiarid alpine region of Northwest China - Zhao, Yonghong; Zhao, Weijun; Fang, Huijun (Frontiers in Forests and Global Change, 2023)
Analyzing the physiological response of trees to climate change in the Qilian Mountains region is key to studying the impact of global change on forest ecosystems in the semiarid alpine region of Northwest China. The leaf area index (LAI) of the canopy of a forest is an important input parameter for simulating carbon and water cycles in forest ecosystems. Studying the relationship between LAI and environmental factors can provide a scientific basis for accurately describing the structure, function, and ecohydrological processes of forest ecosystems and theoretically guide for sustainable management of water conservation in forests. Methods: In this study, the LAI of the Picea crassifolia canopy was monitored for 2 years (2015–2016) by field observations, and its dynamic changes were analyzed. The relations between LAI and air temperature (AT), precipitation (P), soil temperature (ST), and soil water content (SWC) were studied using Pearson's correlation and multiple regression analyses. The results were as follows: seasonal variations in LAI showed a single-peak curve, which first increased, reached a maximum, remained relatively stable, and then decreased. The maximum value was 4.02 and 4.18 relatively observed in mid-August 2015 and 2016. The LAI of the P. crassifolia canopy in different months was positively correlated with AT and P. It was correlated between the LAI of the canopy with ST40−60 in May and June (p < 0.05) and was also highly positively correlated between the LAI of the canopy with ST60−80, STmean, and SWC60−80 in July and August (p < 0.01). There was a positive correlation between the LAI of the canopy with SWC0−60 and SWCmean in July and SWC0−60 and SWCmean in August (p < 0.05). The LAI of the canopy was affected by AT and ST in May and July, AT and P in June, P in August, and P and ST in September. Our study implied that the rapid increase period of the LAI of the canopy was from late May to early July. The LAI of the canopy was more influenced by temperature and water in July and August. In addition, the LAI of the canopy has significant seasonal variation although it is evergreen coniferous tree species.